2016
DOI: 10.1080/13825585.2016.1161001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of HIV disease and older age on laboratory-based, naturalistic, and self-perceived symptoms of prospective memory: does retrieval cue type and delay interval matter?

Abstract: There is a rising prevalence of older HIV+ adults who are at risk of deficits in higher-order neurocognitive functions and associated problems in everyday functioning. The current study applied Multiprocess Theory to examine the effects of HIV and aging on measures of laboratory-based, naturalistic, and self-perceived symptoms of prospective memory (PM). Participants included 125 Younger (48 with HIV, age = 32±4.6 years) and 189 Older (112 with HIV, age = 56±4.9 years) adults. Controlling for global neurocogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…Compared to HIVcontrols, HIV + participants were younger in four studies [43][44][45]50] and older in two studies [29,51]. There were also differences in other demographic factors such as education and ethnicity between HIV + and HIV-participants in 11 studies [40][41][42][43][44][45][50][51][52][53], and they controlled these factors in the analyses.…”
Section: Inclusion Of Hiv-controlsmentioning
confidence: 99%
“…Compared to HIVcontrols, HIV + participants were younger in four studies [43][44][45]50] and older in two studies [29,51]. There were also differences in other demographic factors such as education and ethnicity between HIV + and HIV-participants in 11 studies [40][41][42][43][44][45][50][51][52][53], and they controlled these factors in the analyses.…”
Section: Inclusion Of Hiv-controlsmentioning
confidence: 99%
“…In that study, younger HIV+ adults’ (mean age, 37.5 years) performance was similar to that of older seronegative adults (mean age, 70 years) on tests of learning, delayed memory, processing speed and attention, visuospatial processing, and language, suggesting that the average 40-year old with HIV had the same cognitive status as a healthy 70-year old. A careful review of more recent cART era studies suggests a similar pattern of accelerated neurocognitive aging (e.g., Woods et al 2010; Avci et al 2016). Across many of these studies, a stair-step effect is observed whereby age and HIV have an additive impact on neurocognitive outcomes.…”
mentioning
confidence: 99%
“…Specifically, younger HIV+ groups reliably perform comparably to older HIV− groups, and both of these groups perform more poorly than older HIV+ groups. For example, several papers show that the memory functioning of HIV+ individuals in their mid-30s are comparable to HIV− individuals in their mid-50s (Avci et al 2016; Woods et al 2010; Scott et al 2011). While most studies have reliably shown differences between HIV+ adults and age-matched seronegative comparison subjects (potentially supporting accentuated aging), no studies in the cART era have directly examined whether older HIV+ adults – who may be at greatest risk to experience both accelerated and accentuated aging – evidence neurocognitive profiles similar to those of much older seronegative adults.…”
mentioning
confidence: 99%
“…These earlier studies highlighted the need for a carefully matched SN control population in studies where neurocognitive performance may be associated with aging but may also be impacted by other health and lifestyle factors such as alcohol or tobacco use. More recent neuropsychological studies, reported in the current decade, suggest that age and HIV infection have an additive impact on neurocognitive performance, with younger HIV-infected individuals performing comparably to older SN individuals in neurocognitive tests, suggestive of accelerated aging (Avci et al 2016 ; Scott et al 2011 ; Woods et al 2010 ). Sheppard et al ( 2015 ) started with a group of cognitively normal individuals and tested their neurocognitive performance approximately 14 months later.…”
Section: Neurocognitive Changes and Chronic Hiv Infection: Acceleratementioning
confidence: 94%